Study of Wear, Hardness and Fractography of Millscale Reinforced Ceramic Matrix Composites - Durowaye, Stephen; Sekunowo, Olatunde; Lawal, Ganiyu (Journal of the Institute of Engineering, 2019)
Ceramic matrix composites were developed by powder metallurgy and the blended matrix was reinforced with millscale particles from 3-18 wt.% at particles size distribution of 106-250 μm. Microstructural, hardness and wear characterisations were carried out on the composites using standardised methods. The results showed that the 106 μm millscale particles reinforced composite exhibited desirable hardness value of 124 BHN, low wear rate of 1.99 x 10-6 g/m and appreciable high wear resistance indicating a potential for effective performance in service. The composites worn surfaces revealed abrasion, adhesion and grooves formation. These features derived from the composites microstructure formed the basis on which enhancement procedures could be developed.